Improving Community Health Using an Outcome-Oriented CQI Approach to Community-Engaged Health Professions Education - Clithero, Amy; Ross, Simone Jacquelyn; Middleton, Lyn; Reeve, Carole; Neusy, Andre-Jacques (Frontiers in Public Health, 2017)
Health professionals providing health care services must have the relevant competencies and clinical experiences needed to improve population health outcomes in different contexts. Current models of health profession education often fail to produce a fit-for-purpose workforce ready and willing to provide relevant, quality care to underserved communities. Evidence is emerging that community engaged and socially accountable health workforce education, i.e. aligned with priority health needs, produces a workforce ready and willing to work in partnership with underserved regions. This model of education fosters greater affiliation between education and service delivery systems and requires institutions to measure graduate outcomes and institutional impact. The Training for Health Equity Network (THEnet), a partnership of socially accountable health workforce education institutions, has developed and tested a Social Accountability Framework for Health Workforce Education (The Framework) and toolkit to improve alignment of health workforce education with outcomes to assess how well education institutions meet the needs of the communities they serve. The Framework links education and service delivery creating a CQI feedback loop to ensure that education addresses needs and maximizes impact on the quality of service delivery. The Framework also provides a unifying set of guidelines for health workforce policy and planning, accreditation, education, research, and service delivery. A key element to ensuring consistent high quality service delivery is an appropriately trained and equitably distributed workforce. An effective and comprehensive mechanism for evaluation is the method of Continuous Quality Improvement (CQI). An effective and comprehensive mechanism for Continuous Quality Improvement (CQI) links the design,